On the 3D void formation of hybrid carbon/glass fiber composite laminates: A statistical approach - Monticeli, Francisco M. [UNESP] (2020)
This work aims at assessing the effect of the stacking sequence of hybrid laminates on the 3D void formation through a statistical approach. For that purpose, a three-dimensional microstructure is created from multiple two-dimensional microscopy images. Weibull approach shows a poorer fit for carbon fiber composite, while the presence of glass fiber creates homogenization in porosity variation, also treated by ANOVA. The present methodology enables the prediction of void volume fraction in different carbon/glass preform ratios and stacking sequence along the laminate length and through-thickness. The low glass fiber ratio decreases the void content, homogenized porosity distribution along laminate length, and thickness, mainly for glass fiber preforms located in the middle of the laminate. These results confirm that the uniformity of void content throughout the composite can be improved by altering the stacking sequence and ratio of glass to carbon fiber preforms. This methodology can be extended to any composite manufacturing process